Evolutionary multi-objective route and fleet assignment optimisation for regular and non-regular flights. (2016) - Takadama, Keiki; Jinba, Takahiro; Harada, Tomohiro; Sato, Hiroyuki
To optimise the flight schedule that consists of: 1) the regular flight operated on the same day and time through one year; 2) the non-regular flight operated on the different day and time according to month, this paper proposes the new multi-objective fleet assignment method that considers both the regular and non-regular flights. To investigate the effectiveness of our method, this paper applies it to Japanese domestic airport network optimisation for two months, on- and off-peak months, using a real-world data. The intensive simulation have revealed that the following implications: 1) our method can evolve a flight network that can be applied into the on- and off-peak month; 2) our method can find a flight network that has a well-balanced profit between on- and off-peak months; 3) in peak month, our method can find a flight network that has higher profit.